Experimental dynamic collapse response of post-and-beam mass timber frames under a sudden column removal scenario. (15th April 2021) - Cheng, Xinyi; Gilbert, Benoit P.; Guan, Hong; Underhill, Ian D.; Karampour, Hassan
Highlights: Collapse dynamic response of post-and-beam mass timber frames was studied. Failure modes under dynamic scenarios were found to be the same as static ones. Structural behaviours under dynamic and static scenario were compared. DIF values greater than 2.0 were found for brittle failure modes. A proposed DIF value of 1.5 was found to be reasonable for ductile failure modes. Abstract: In this study, an experimental program was carried out to investigate the dynamic behaviour of post-and-beam mass timber frames, manufactured from LVL structural products, under a sudden column removal scenario. Twenty-five free-fall and two additional static tests were performed on scaled-down frames assembled with three beam-to-column connection types, referred to as "Double-beam", "Megant type" and "T-section", currently used in mass timber buildings. The structural responses, failure modes and dynamic increase factors (DIF) are presented and discussed. For frames assembled with connections exhibiting a brittle failure in the timber, the cracks were found to develop earlier in dynamic tests than in static tests, resulting in large experimental DIF values over 2.0. However, for connections displaying ductile failure modes, the design DIF value of 1.5 proposed in the literature was found to be reasonable. Pseudo-static responses were calculated and found to be inconsistent in predicting the dynamic responses. This paper presents an essential understanding of the dynamic behaviour of post-and-beam mass timber frames and lay the foundation for future further studies aiming at investigating the dynamic responses of the entire post-and-beam mass timber buildings with, e.g. cross laminated timber (CLT) floors.